Clinical development of galunisertib (LY2157299 monohydrate), a small molecule inhibitor of transforming growth factor-beta signaling pathway - Herbertz, Stephan (Drug Des Devel Ther, 2015)
Transforming growth factor-beta (TGF-β) signaling regulates a wide range of biological processes. TGF-β plays an important role in tumorigenesis and contributes to the hallmarks of cancer, including tumor proliferation, invasion and metastasis, inflammation, angiogenesis, and escape of immune surveillance. There are several pharmacological approaches to block TGF-β signaling, such as monoclonal antibodies, vaccines, antisense oligonucleotides, and small molecule inhibitors. Galunisertib (LY2157299 monohydrate) is an oral small molecule inhibitor of the TGF-β receptor I kinase that specifically downregulates the phosphorylation of SMAD2, abrogating activation of the canonical pathway. Furthermore, galunisertib has antitumor activity in tumor-bearing animal models such as breast, colon, lung cancers, and hepatocellular carcinoma. Continuous long-term exposure to galunisertib caused cardiac toxicities in animals requiring adoption of a pharmacokinetic/pharmacodynamic-based dosing strategy to allow further development. The use of such a pharmacokinetic/pharmacodynamic model defined a therapeutic window with an appropriate safety profile that enabled the clinical investigation of galunisertib. These efforts resulted in an intermittent dosing regimen (14 days on/14 days off, on a 28-day cycle) of galunisertib for all ongoing trials. Galunisertib is being investigated either as monotherapy or in combination with standard antitumor regimens (including nivolumab) in patients with cancer with high unmet medical needs such as glioblastoma, pancreatic cancer, and hepatocellular carcinoma. The present review summarizes the past and current experiences with different pharmacological treatments that enabled galunisertib to be investigated in patients.